2009
DOI: 10.4161/psb.4.1.7487
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic compounds from roots ofCentaurea diffusaLam.

Abstract: An extract of roots of Centaurea diffusa (diffuse knapweed) yielded caryophyllene oxide and linoleic acid which were shown to be phytotoxic. Also isolated were germacrene B, a previouslyknown phytotoxin as well as the inactive polyene aplotaxene. A combination of these compounds, if transferred to the soil, could be one factor in the invasive behavior of this weed. Contrary to a literature report, 8-hydroxyquinoline was not detected in root exudates of in vitro grown C. diffusa nor could it be identified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Linoleic, oleic and palmitic acids are well-known allelochemicals (Macias et al 2006 ;Noguchi 2008 ;Quintana et al 2009 ). Regardlessly, the study of Angelini et al ( 2015 ) is the fi rst report in which their effects on the weeds of truffl e plants ( L. corniculatus , M. ciliate and S. vulgaris ) were exposed.…”
Section: Growth Inhibitory Effects (Ir) Of Isolated Allelochemicalsmentioning
confidence: 99%
“…Linoleic, oleic and palmitic acids are well-known allelochemicals (Macias et al 2006 ;Noguchi 2008 ;Quintana et al 2009 ). Regardlessly, the study of Angelini et al ( 2015 ) is the fi rst report in which their effects on the weeds of truffl e plants ( L. corniculatus , M. ciliate and S. vulgaris ) were exposed.…”
Section: Growth Inhibitory Effects (Ir) Of Isolated Allelochemicalsmentioning
confidence: 99%
“…Quintana et al (2009) showed that linoleic acid was phytotoxic in L. sativa and that the toxicity of fatty acids increases with an increase in double bonds. The phytotoxic properties of fatty acids are well known and understood.…”
Section: Resultsmentioning
confidence: 99%
“…This remarkable difference was mainly due to species distinction and other complex factors (e.g., habitat and harvest time) (Sancholle et al 1988;Tang et al 2011). The allelopathic effects of FFAs are frequently observed during bioassay-guided fractionation of extracts from a variety of organisms (Kroes 1972;Song et al 2004;Quintana et al 2009). The modes of action of most natural phytotoxins are unknown, especially for compounds thought to be involved in plant/plant interactions (allelochemicals) (Duke et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Mutually exclusive protein groups were affected by the two chemicals (Duke et al 2013). Linoleic, oleic and palmitic acids have already been isolated as allelopathic substances (Rice 1995;Macías et al 2006;Quintana et al 2009;Noguchi et al 2008) but in this study they are tested for the first time on weeds of truffle plants (L. corniculatus, M. ciliata and S. vulgaris).…”
Section: Discussionmentioning
confidence: 98%